Athletes' experiences of social support during their transition out of elite sport: An interpretive phenomenological analysis. (May 2018) - Brown, Christopher J.; Webb, Thomas L.; Robinson, Mark A.; Cotgreave, Rick
Abstract: Objectives: The sources and types of social support that athletes receive during the transition out of sport have been well documented. However, less is known about how athletes perceive, mobilise, and manage supportive relationships. This study aimed therefore to gain a more comprehensive insight into the ways that social support may influence how athletes adjust to life following retirement from elite sport. Design: The study was designed according to the principles of Interpretative Phenomenological Analysis. Method: Eight former British elite athletes (four male and four female) from eight different Olympic sports were recruited using criterion-based purposive sampling strategies. Data collected using semi-structured interviews were analysed to explore subjective experiences of social support during transition. Results: Participants' perception of feeling cared for and understood enabled support to be effective. There were variations in participants' ability to seek out and ask for support and those who found this difficult also found transition a more distressing experience. As transitions progressed, the adjustment process was closely linked to the participant's evolving sense of self. New social relationships and social roles fostered a sense of feeling supported, as well as providing opportunities to support others (e.g., other retired athletes). Providing support helped the participants to experience a sense of growth that facilitated adjustment to life after sport. Conclusions: The content of support was largely dependent on context; that is, perceptions of supporters were just as important, if not more so, than specific support exchanges. Stigma around asking for help was a barrier to support seeking. Highlights: Appraising supporters as caring and understanding enabled support to be effective. Family and peers (other retired athletes) were the most effective supporters. Participants often found it difficult to seek support and ask for help. Social support played a positive role in reshaping the participants' sense of self. Providing support to others was just as effective as receiving support.